Differential regulation of monocarboxylate transporter 8 expression in thyroid cancer and hyperthyroidism. Issue 3 (September 2017) - Badziong, Julia; Ting, Saskia; Synoracki, Sarah; Tiedje, Vera; Brix, Klaudia; Brabant, Georg; Moeller, Lars Christian; Schmid, Kurt Werner; Fuhrer, Dagmar; Zwanziger, Denise
Abstract : Objective: Thyroid hormone (TH) transporters are expressed in thyrocytes and most play a role in TH release. We asked whether expression of the monocarboxylate transporter 8 (MCT8) and the L-type amino acid transporters LAT2 and LAT4 is changed with thyrocyte dedifferentiation and in hyperfunctioning thyroid tissues. Design and methods: Protein expression and localization of transporters was determined by immunohistochemistry in human thyroid specimen including normal thyroid tissue (NT, n  = 19), follicular adenoma (FA, n  = 44), follicular thyroid carcinoma (FTC, n  = 45), papillary thyroid carcinoma (PTC, n  = 40), anaplastic thyroid carcinoma (ATC, n  = 40) and Graves' disease (GD, n  = 50) by calculating the 'hybrid' (H) score. Regulation of transporter expression was investigated in the rat follicular thyroid cell line PCCL3 under basal and thyroid stimulating hormone (TSH) conditions. Results: MCT8 and LAT4 were localized at the plasma membrane, while LAT2 transporter showed cytoplasmic localization. MCT8 expression was downregulated in benign and malignant thyroid tumours as compared to NT. In contrast, significant upregulation of MCT8, LAT2 and LAT4 was found in GD. Furthermore, a stronger expression of MCT8 was demonstrated in PCCL3 cells after TSH stimulation. Conclusions: Downregulation of MCT8 in thyroid cancers qualifies MCT8 as a marker of thyroid differentiation. The more variable expression of LATs in distinct thyroid malignancies may be linked with other transporter properties relevant to altered metabolism in cancer cells, i.e. amino acid transport. Consistent upregulation of MCT8 in GD is in line with increased TH release in hyperthyroidism, an assumption supported by our in vitro results showing TSH-dependent upregulation of MCT8.